2020
DOI: 10.1002/jms.4579
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase studies of copper(I)‐mediated CO2 extrusion followed by insertion of the heterocumulenes CS2 or phenylisocyanate

Abstract: The gas-phase extrusion-insertion reactions of the copper complex [bathophenanthroline (Bphen)Cu I (O 2 CC 6 H 5 )] 2− , generated via electrospray ionization, was studied in a linear ion trap mass spectrometer with the combination of collisioninduced dissociation (CID) and ion-molecule reaction (IMR) events. Multistage mass spectrometry (MS n ) experiments and density functional theory (DFT) demonstrated that extrusion of carbon dioxide from [(Bphen)Cu(O 2 CC 6 H 5 )] 2− (CID) gives the organometallic interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(44 reference statements)
0
2
0
1
Order By: Relevance
“…O'Hair 等 [13] 通过理论计算研究探索了铜催化异氰酸酯 氢芳基化的反应机理. 他们发现, 当芳基铜(I)物种生成 后, 异氰酸酯的碳氧双键插入活化能仅为 15.4 kcal/mol, 远远低于碳氮双键插入的活化能.…”
Section: 子中间体中 形式负电荷可被氧原子和氮原子分享 因 此较为稳定 可作为活性中间体参与后续反应历程unclassified
“…O'Hair 等 [13] 通过理论计算研究探索了铜催化异氰酸酯 氢芳基化的反应机理. 他们发现, 当芳基铜(I)物种生成 后, 异氰酸酯的碳氧双键插入活化能仅为 15.4 kcal/mol, 远远低于碳氮双键插入的活化能.…”
Section: 子中间体中 形式负电荷可被氧原子和氮原子分享 因 此较为稳定 可作为活性中间体参与后续反应历程unclassified
“…Our initial report on transformation of the anionic copper acetate complex [(CH 3 )Cu(O 2 CCH 3 )] − to the anionic copper(I) dithioacetate complex [(CH 3 )Cu(S 2 CCH 3 )] − [17] convinced us that guided by mechanistic studies, these extrusion-insertion (ExIn) reactions could potentially be harnessed for one-pot organic synthetic methods for a wide range of new species including thioamides, amidines, amides, alkenes and ketones (Eqn 1, Scheme 1a). [18][19][20][21][22][23][24] In potential competition with the desired products is the protodecarboxylation side reaction (Eqn 2, Scheme 1a and Cycle B, Scheme 1b). [25,26] Fortunately, comprehensive investigations by Kozlowski's group into the scope of the palladium-catalysed protodecarboxylation side reaction identified potential solvent and additives that suppress this reaction, [25] which provided a valuable starting point in our solution-phase investigations.…”
Section: Introductionmentioning
confidence: 99%
“…CID of the adduct [CH 3 CuS 2 CCH 3 ] − gives CH 3 CS 2 − . Subsequently we showed that the copper complex [(Bphen)Cu(O 2 CC 6 H 5 )] 2− (Bphen=bathophenanthroline) also undergoes decarboxylation and the resultant organometallic complex, [(Bphen)Cu(C 6 H 5 )] 2− , reacts with CS 2 to form [(Bphen)Cu(S 2 CC 6 H 5 )] 2− [86] . These studies highlighted that sequential extrusion and insertion reactions could be used to transform coordinated ligands and spurred us onto the development of the new class of reactions coined as ExIn (Extrusion‐Insertion), which are discussed in detail below [87] …”
Section: Introductionmentioning
confidence: 99%